Fluoroquinolone Resistance: An Overview - DACKOUO, Blaise (European Journal of Applied Sciences, 2022)
In this review, we addressed different types and mechanisms of resistance to fluoroquinolones. Strategies to overcome resistance to these antimicrobials were discussed. The study showed that resistance by efflux was the reported type of mechanism of resistance varied with bacteria stains. For Enterobacteriaceas, plasmid mediated genese were responsible of the resistance but In Shigella, the resistance was due to chromosomal mutation. Helicobacter, Pseudomonas, Enterobacteria, Mycobacteria were found to be the most resistant microorganisms. To face the situation many strategies are usable such as rational antibiotic prescription, new compound discovery, antimicrobial and stewardships. The AWaRe concept is recently developed by the WHO as powerful tool to overcome antibiotic resistance.